ASSESSING THE ETHNOMATHEMATICAL VALUES OF GUDEG JOGJA: A QUALITATIVE INQUIRY INTO THREE-DIMENSIONAL SPATIAL DECOMPOSITION AND SEQUENTIAL PROGRAMMING - Wuri Astiwi; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2026)
This study aims to identify and analyze mathematical concepts embedded in the processing of Gudeg Yogyakarta through an ethnomathematical approach. The research employed a qualitative method with an educational ethnographic design. The research subjects consisted of traditional gudeg producers, besek craftsmen, and home-based gudeg industry practitioners in the Yogyakarta region, selected purposively. Data were collected through participant observation, in-depth interviews, and visual documentation to capture cultural practices and the underlying mathematical meanings. Data analysis was conducted descriptively and analytically through the stages of data reduction, data display, and conclusion drawing by transforming cultural activities into formal mathematical representations. The results indicate that the gudeg processing process contains various mathematical concepts, including three-dimensional and plane geometry in raw materials and packaging, fractions and ratios in ingredient measurements, sequences and series in the canning process, and algorithmic logic in deep cooking techniques. These findings confirm that Gudeg Yogyakarta has significant potential as a meaningful, contextual mathematics learning resource grounded in local wisdom.